Strengthening of Long RC Columns Using Near Surface Mounted GFRP Bars - Romaih, Ahmed (AUC Knowledge Fountain, 2022)
Many of the existing reinforced concrete (RC) columns are deficient because of numerous reasons such as increase in service loads, deterioration due to environmental attacks, errors in the design and/or construction phase or in the worst case, accidents. These elements require strengthening or repair. Different methods have been developed over the years for solving different rehabilitation problems. Recently, advanced composites used for external bonding in the form of fabrics or laminates have become an accepted method. The use of Fibre-Reinforced Polymers (FRPs) in this process is a promising technology, especially that these materials are corrosion-free. One of the new techniques used for strengthening is placing Near-Surface Mounted (NSM) FRP bars in the existing structural elements. The aim of this research is to examine the effectiveness of strengthening reinforced concrete (RC) columns using NSM glass fibre reinforced polymer (GFRP) bars. Seventeen columns with a cross-section of 250 × 250 mm will be cast and tested under the effect of axial loads and uniaxial bending. The test parameters include different slenderness ratios as well as the length and diameter of the NSM GFRP bars. The results are interpreted to analyze the effectiveness of using NSM GFRP bars in strengthening RC columns and to test whether they can be used as efficiently as steel/concrete jackets or CFRP sheets. The performance of the strengthened columns are evaluated based on the measured load-deflection curves, the ultimate observed strength, and the crack width and spacing at estimated service load. The experimental investigation proved that NSM GFRP bars can be effectively used to strengthen RC columns as GFRP bars have an advantage over CFRP due to low cost relative to CFRP. It is lighter, has a higher resistance to corrosion, and has a higher tensile strength with an ease of use relative to steel plates. It is also maintenance free, meaning that there will be no rehabilitation cost.